Content Reliability Measurement of Holistic Approach Training Module - Muhamad Afzamiman, Aripin; Sarimah, Ismail; Rohana, Hamzah; Ros Eliana, Ahmad Zuki (Academic Publications, 2018)
As part of correctional programme components, the significant role of vocational instructor in prison is not only about delivering skills, but also to improve inmates attitude and perspective about life. Therefore, the Holistic Approach in Correctional Education (HACE) Training Module was developed, to provide awareness and skills in training in mates as a whole among prisons vocational instructors. In addition, this module focused on the integration of God Consciousness element as a compass of life; internally and externally without disturbing the classic objective in vocational training. The development of HACE Module comprised a total of fourteen activities, structured based on modified All Quadrant All Level (AQAL) Model